Dataset of the sperm proteome of stallions with different motility - Gemma Gaitskell-Phillips; Francisco E. Martín-Cano; José M Ortiz-Rodríguez; Antonio Silva-Rodríguez; Eva da Silva-Álvarez; Maria C. Gil; Cristina Ortega-Ferrusola; Fernando J. Peña (Data in Brief, 2022)
This paper provides a detailed set of data on how the stallion sperm proteome differs among stallions with different sperm motilities, although within normal ranges. Findings distinguish proteins that may help to identify stallions of superior sperm motility. Sperm proteins were analyzed using a UHPLC/MS/MS system comprising of an Agilent 1290 infinity series UHPLC coupled to an Agilent 6550 Q-TOF mass spectrometer (Agilent Technologies, Santa Clara, CA, USA). These data can be used to disclose potential targets to identify good sperm samples and to study specific pathways involved in the regulation of sperm motility. This data article is linked to the paper “Proteins involved in mitochondrial metabolic functions and fertilization predominate in stallions with better motility Journal of Proteomics 247:104335 doi: 10.1016/j.jprot.2021.104335”.